Biomaterial Material Applications in Postoperative Surgical Fields of Uvulopalatopharyngoplasty: A Comparative Study - Tsung-Che Yu; Ting-Chieh Huang; Po-Yueh Chen; Chun-Che Shih; Wei-Wen Chang (Journal of Functional Biomaterials, 2023)
This retrospective study compared the effectiveness of different materials used in Uvulopalatopharyngoplasty (UPPP) for snoring or obstructive sleep apnea treatment, focusing on the impact on bleeding control, pain control, and healing ability. The study population comprised 213 patients who underwent UPPP at Wan-Fang Hospital between July 2018 and October 2022 divided into four groups based on the postoperative material used: No Material Use Group, Tissue Glue Group, Platelet-Rich Plasma (PRP) Group, and Polyglycolic Acid (PGA) Sheet Group. Results showed significant differences in operation time and intraoperative bleeding amount among the groups, with the Tissue Glue Group demonstrating the shortest operation time. While no significant differences in postoperative pain at 24 h were observed, PRP and PGA Sheet groups exhibited lower average pain scores in cases with higher pain levels. Postoperative complications and emergency room visits due to pain or bleeding varied among the groups, with the No Material Use Group having the highest incidence, although no statistical significance was achieved. This study provides insights into the potential benefits of using advanced materials in UPPP, guiding future research and clinical practice to improve patient care and outcomes.